Dispersion pattern of 226Ra and 235U using the ERICA Tool in the coastal mining area, Ierissos Gulf, Greece. (March 2019) - Pappa, F.K.; Tsabaris, C.; Patiris, D.L.; Androulakaki, E.G.; Ioannidou, A.; Eleftheriou, G.; Kokkoris, M.; Vlastou, R.
Abstract: Natural radionuclides, present in mining materials, can exhibit elevated values, thus it is of great interest to study their dispersion in mining areas. Radionuclide spatial variations were determined in coastal surface sediments near the mining area of Ierissos Gulf in northern Greece. 226 Ra and 235 U measured concentrations were compared with the estimations of ERICA Tool, the dispersion patterns were derived and the affected region around the load-out pier area was calculated to be approximately 21 km 2 . Highlights: 226 Ra and 235 U spatial distribution indicated elevated values near Stratoni port. The 226 Ra concentrations at Stratoni port were higher than the soil world median. The applied dispersion model determined the dispersion pattern. The affected area due to mining activities was estimated approximately 21 km 2 .